"Snap-kicking" in elite Australian football: How foot preference and task difficulty highlight potential benefits from bilateral skill training - Moore, B. B.; O'Dwyer, N. J.; Adams, R. D.; Cobley, S. (International Journal of Performance Analysis in Sport, 2017)
"Snap-kicks" in Australian Football (AF) occur when players can potentially score but are facing away from the goal, necessitating a kick across the body or over the opposite shoulder. In games, situations arise for both right- and left-foot snaps, but players often strive to use their preferred rather than non-preferred foot. We consider whether such a strategy is optimal and in this study examine whether foot preference and task difficulty affect snap-accuracy. Accordingly, 27 elite AF players (19 "right-footers", 8 "left-footers") were tasked with executing snap-kicks at easy and more difficult (acute) angles using both feet. As expected, accuracy was greater with the preferred (76%) than the non-preferred foot (57%) and greater for easy (78%) than difficult kick angles (56%), however there were no accuracy differences due to player footedness. Surprisingly, given the relative difficulty, snap-kicks from the more difficult angle with the preferred foot could be made with a similar level of accuracy (67%) to kicks with the non-preferred foot from the easier angle (69%). Results suggest that using the non-preferred foot for snap-kicks at goal in appropriate situations during games could increase scoring affordances, and that training on the non-preferred foot may benefit individual and team performance.